Recommendations and requirements for the design of bioanalytical testing used in comparability studies for biosimilar drug development. (March 2011) - Cai, Xiao-Yan; Gouty, Dominique; Baughman, Sharon; Ramakrishnan, MS; Cullen, Constance
With the imminent expiry of patents on a number of biological products on the market, the development of biosimilars (or ''follow-on biologics'') creates an increasing opportunity in the biotechnology industry. Although general guidelines on the quality and safety of biological products also apply to biosimilars, there is a need to address specific requirements for developing biosimilar drugs. Since it is critical to show comparability of the biosimilar products to their reference (or innovator) products, developing the appropriate bioanalytical methods to support such preclinical and clinical comparability studies is of great importance. The present work recommends the requirements for the development and validation for both pharmacokinetic and immunogenicity assays to support the biosimilar drug development.